Hubungan Fungsi Ginjal dengan Kejadian Demensia Vaskular di RSPAD Gatot Soebroto 2023-2024 - Afralia, Aqila Fayza; Astari, Riezky Valentina; Saleh, Arman Yurisaldi; Dandanah, Maulidya Ayudika (Jurnal Kedokteran Meditek, 2025)
Introduction: Vascular dementia is the second most common type of dementia in the world, following Alzheimer's dementia. One of the primary risk factors for vascular dementia is hypertension. Prolonged hypertension can impair kidney function, as indicated by the glomerular filtration rate (GFR). A decreased GFR can lead to vascular complications, such as endothelial dysfunction, which may result in brain tissue infarction and contribute to the development of vascular dementia in the future. Purpose: The purpose of this research is to examine the relationship between kidney function, measured through GFR values, and the incidence of vascular dementia at Gatot Soebroto Army Hospital during the 2023-2024 period. Methods :  This study employed a cross-sectional design and conducted a bivariate test using the Chi-square method with a sample of 47 individuals. The research utilized a total sampling technique. Results: Among the 47 patients, 35 (74.5%) were diagnosed with vascular dementia, while 12 (25.5%) had different types of dementia. The majority of patients, 31 (66%), exhibited a mild decrease in GFR values. The analysis revealed a relationship between kidney function and the incidence of vascular dementia, with a p-value of 0.596. Conclusion:  There was no significant relationship found between kidney function, as indicated by GFR values, and the incidence of vascular dementia. Future researchers can study larger populations.